Systematic Thinking for Social Action - Rivlin, Alice M. (H. Rowan Gaither lectures in systems science., 2015)
In January 1970 Alice M. Rivlin spoke to an audience at the University of California-Berkeley. The topic was developing a more rational approach to decisionmaking in government. If digital video, YouTube, and TED Talks had been inventions of the 1960s, Rivlin's talk would have been a viral hit. As it was, the resulting book, Systematic Thinking for Social Action, spent years on the Brookings Press bestseller list. Is is a very personal and conversational volume about the dawn of new ways of thinking about government. As deputy assistant secretary for program coordination, and later as assistant secretary for planning and evaluation, at the Department of Health, Education and Welfare from 1966 to 1969, Rivlin was an early advocate of systems analysis, which had been introduced by Robert McNamara at the Department of Defense as PPBS (planning-programming-budgeting-system). While Rivlin brushes aside the jargon, she digs into the substance of systematic analysis and a 'quiet revolution in government. In an evaluation of the evaluators, she issues mixed grades, pointing out where analysts had been helpful in finding solutions and where--because of inadequate data or methods--they had been no help at all. Systematic Thinking for Social Action offers important insights for anyone interested in working to find the smartest ways to allocate scarce funds to promote the maximum well-being of all citizens.